2020
DOI: 10.1136/bmjopen-2019-033895
|View full text |Cite|
|
Sign up to set email alerts
|

Factors influencing the utilisation of free-standing and alongside midwifery units in England: a qualitative research study

Abstract: ObjectiveTo identify factors influencing the provision, utilisation and sustainability of midwifery units (MUs) in England.DesignCase studies, using individual interviews and focus groups, in six National Health Service (NHS) Trust maternity services in England.Setting and participantsNHS maternity services in different geographical areas of England Maternity care staff and service users from six NHS Trusts: two Trusts where more than 20% of all women gave birth in MUs, two Trusts where less than 10% of all wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 31 publications
4
46
0
Order By: Relevance
“…Systematic barriers related to gender, professional, economic, and social disempowerment intersect with “powerful precedents” to constrain midwifery's progress globally (p. 397) 8 . Obstacles persist to establishing the full scope of midwifery practice, including the normalization of MUs 2,8,9 . Ethnographic studies have explored aspects of organizational culture, which support MUs, such as quality of leadership, equitable power dynamics, supportive interprofessional and intraprofessional relationships, and the development of midwifery skills and confidence 10‐12 …”
Section: Introductionmentioning
confidence: 99%
“…Systematic barriers related to gender, professional, economic, and social disempowerment intersect with “powerful precedents” to constrain midwifery's progress globally (p. 397) 8 . Obstacles persist to establishing the full scope of midwifery practice, including the normalization of MUs 2,8,9 . Ethnographic studies have explored aspects of organizational culture, which support MUs, such as quality of leadership, equitable power dynamics, supportive interprofessional and intraprofessional relationships, and the development of midwifery skills and confidence 10‐12 …”
Section: Introductionmentioning
confidence: 99%
“…This represents a 3% saving on the current budget of £2.6B for maternity care. 7 In addition, our survey showed that MUs were not equally distributed across the country. One-third of local maternity services had no MUs, whereas others achieved 20% of all births in these facilities (designated 'high performing'), and the remainder had MUs but they were frequently underutilised, with < 10% of all births in MUs (designated 'low performing').…”
Section: Introductionmentioning
confidence: 84%
“…Potentially, this could represent around 45,000 low-risk women per year in England who could birth in a MU but currently have no access to one or are not using existing ones. 7 The mapping exercise also described suboptimal organisational processes within MUs, with the frequent movement of staff out of them to work on OUs and the regular closure of MUs as a consequence. Access to MUs was frustrated by the absence of a streamlined care pathway during pregnancy and inadequate mechanisms for service users to obtain information and exercise choice about and for them.…”
Section: Chapter 7 Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…MUs can also encourage innovative ways of providing care and foster fulfilment and empowerment for midwives (Walsh 2007 , 2009 ). However, Walsh et al ( 2020 ) found significant obstacles to MUs reaching their full potential. These included a lack of commitment from healthcare providers to establish MUs as part of essential maternity service provision, an absence of leadership to drive change and lack of capacity and willingness to address women’s information needs.…”
Section: Innovations For Midwives and Midwiferymentioning
confidence: 99%